2008
DOI: 10.1002/pmic.200800109
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of exosomes: Current perspectives

Abstract: Exosomes are 40-100 nm membrane vesicles of endocytic origin secreted by most cell types in vitro. Recent studies have shown that exosomes are also found in vivo in body fluids such as blood, urine, amniotic fluid, malignant ascites, bronchoalveolar lavage fluid, synovial fluid, and breast milk. While the biological function of exosomes is still unclear, they can mediate communication between cells, facilitating processes such as antigen presentation and in trans signaling to neighboring cells. Exosome-like ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
675
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 784 publications
(699 citation statements)
references
References 146 publications
17
675
0
7
Order By: Relevance
“…38); even so, a release of exosomes by MCF-7 has been shown (39). Excepting our study and the article of Bebawy et al (25), P-gp was not previously identified in the proteome analysis of exosomes (40). However, another ABC transporter, the MRP2 protein, has been found in exosomes isolated from ovarian carcinoma cells (41).…”
Section: Discussionmentioning
confidence: 49%
“…38); even so, a release of exosomes by MCF-7 has been shown (39). Excepting our study and the article of Bebawy et al (25), P-gp was not previously identified in the proteome analysis of exosomes (40). However, another ABC transporter, the MRP2 protein, has been found in exosomes isolated from ovarian carcinoma cells (41).…”
Section: Discussionmentioning
confidence: 49%
“…Mean values Ϯ SEM of three independent experiments are indicated. actin, and GAPDH, which all have been found in exosomes (Simpson et al, 2008), and proteins of the endoplasmic reticulum, such as PDI, were also detected in cell lysates and in exosomes from cultures enriched in cortical astrocytes (Fig. 5C).…”
Section: Synapsin Is Present In Exosomes Isolated From Astrocyteenricmentioning
confidence: 94%
“…[31][32][33] Recently, TSPAN8 was identified as an exosome component in the human colon cancer cell line HT29 by use of a mass spectrometry-based approach. 34,35 Exosomes have been shown to have a role in communication processes between cells by transporting proteins and mRNA molecules that regulate gene expression in target cells. 36 Indeed, TSPAN8 was recently shown to contribute to the recruitment of proteins and mRNA into exosomes and induce angiogenesis in target tissues.…”
Section: Discussionmentioning
confidence: 99%